2018
DOI: 10.7759/cureus.2747
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Primary Headache Syndromes in Patients with a Major Depressive Disorder

Abstract: PurposeThe primary objective of this study was to assess the overall frequency of primary headaches in subjects with a moderate to severe major depressive disorder. A further objective was to determine the frequency of primary headache sub-types in this population.Materials and methodsThis descriptive, cross-sectional study was conducted at the outpatients’ clinic of the department of psychiatry, Pakistan Railways Teaching Hospital, an affiliate of Islamic International Medical College, Rawalpindi. The duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Many medical conditions are more common in people with migraine compared to the general population [33]. There is a small body of literature examining rates of single medical conditions among people with and without migraine, and over the past decade, a growing body of literature has emerged examining the effect of headache day frequency on rates of migraine comorbidities and the effects of selected comorbidities on headache progression [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][22][23][24][25][26][27][28]. After adjusting for sociodemographic variables, the cohort with migraine was about three times more likely to report a medical diagnosis of insomnia, depression, anxiety, and gastric ulcer/GI bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many medical conditions are more common in people with migraine compared to the general population [33]. There is a small body of literature examining rates of single medical conditions among people with and without migraine, and over the past decade, a growing body of literature has emerged examining the effect of headache day frequency on rates of migraine comorbidities and the effects of selected comorbidities on headache progression [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][22][23][24][25][26][27][28]. After adjusting for sociodemographic variables, the cohort with migraine was about three times more likely to report a medical diagnosis of insomnia, depression, anxiety, and gastric ulcer/GI bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidity is the greater than chance association between the two conditions in the same individual [2]. There are many comorbidities associated with migraine including cardiovascular disorders (i.e., stroke, myocardial infarction [3][4][5][6][7][8][9][10], psychiatric disorders (i.e., depression, anxiety, panic disorder, bipolar disorder, personality disorders, suicide attempts) [11][12][13][14][15][16][17][18][19][20][21], neurologic diseases (i.e., epilepsy), sleep conditions (i.e., insomnia, restless leg syndrome, sleep apnea, poor sleep quality and duration) [22][23][24], inflammatory conditions (i.e., allergic rhinitis, asthma) [25,26] as well as chronic pain conditions (i.e., fibromyalgia) [27], among many others [28]. Many comorbidities have been identified as risk factors for progression to chronic migraine [29] and recent work has shown that the combination of comorbidities or "multimorbidity" is associated with medication overuse and new onset CM [30,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muneer et al conducted a study in which he assessed the frequency of primary headache syndrome among patients with major depressive disorder. His results demonstrate that around one-third of patients with depression have any of one underlying chronic headache syndromes [14]. There can be an underlying association between chronic headache syndromes and depression and further studies are required to evaluate it.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a big longitudinal study showed that people who present anxiety traits in their twenties are more prone to develop MDD in their thirties (Gustavson et al, 2018). Also Parkinson's, Migrains' , Alzheimer's patients, among others, have high prevalence of MDD (Ketharanathan et al, 2014;Muneer et al, 2018;Tao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%